THE INFLUENCE OF LEARNING ACCOUNTING PROFESSIONAL ETHICS, COGNITIVE STYLE, AND LOVE OF MONEY ON ACCOUNTING STUDENTS' PERCEPTIONS ABOUT FRAUD - hajrah, Hajrah; Rini Sulistiyanti; wahyuni, Wahyuni (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to determine the influence of learning accounting professional ethics, cognitive style, and love of money on accounting students' perceptions of fraud. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. Data collection in this research used a questionnaire. Questionnaires were distributed to 69 accounting students Class of 2020 at Muhammadiyah University of Makassar. In this research, the data source used is primary data. The research instrument uses the Likert scale method. The data collected was processed using multiple linear regression analysis methods with the help of SPSS Version 26. The results of this research show that: (1) Learning accounting professional ethics has a positive and significant effect on accounting students' perceptions regarding fraud, (2) Cognitive style has a positive and significant effect on accounting students' perceptions regarding fraud, (3) love of money has a positive and significant effect on accounting students' perceptions regarding fraud.